Diferensiasi Metode Penentuan Awal Bulan Hijriyah: Kajian Perspektif Teori Evolusi Sosial Herbert Spencer - M Basthoni (Prodi Antropologi Fakultas Ilmu Budaya Universitas Diponegoro, 2018)
THE – method of determining the beginning of the month of Hijrah is constantly differentiated. Several approaches have been made by experts to understand the phenomenon, both the socio-cultural comparison approach between the conditions of the Prophet Muhammad's time and the current conditions as well as the astronomical-normative approach to verses that have been the root of these differences of opinion. In contrast to previous studies, this paper tries to find the pattern of the differentiation phenomenon and the background of the occurrence with the perspective of Social Evolution Theory proposed by Herbert Spencer. This study shows that the phenomenon of differentiation is a natural process that sequentially follows the following patterns and stages. (1) the stage of increasing the size, (2) the stage of the complexification, (3) the differentiation stage, and (4) the integration stage.